Pengaruh Model Problem Based Learning (PBL) terhadap Kemandirian dan Hasil Belajar Kognitif Siswa - Islami, Izwaldi; Utami, Septiana Dwi; Efendi, Ismail (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The purpose of this study was to: 1) determine the effect of the problem based learning model on students' learning independence; and 2) determine the effect of the problem based learning model on students' cognitive learning outcomes. This type of research is quasi-experimental with a population of all 6 classes of grade VII students at MTs. Nurul Hakim, Kediri District, West Lombok Regency. with a purposive sampling technique, VII D as the experimental class and class VII F as the control class. The instruments used were independence questionnaires and students' cognitive learning outcome test questions. Data collection techniques used pre-test and post-test. While data analysis used interpretation of learning independence categories and a t-test was conducted for cognitive learning outcomes. The results showed that the average value of the pre-test for student independence was 63.52 with a moderate category, and the post-test for student independence had an average value of 64.92 with a moderate category. Students' cognitive learning outcomes showed that the pre-test had an average value of 54.8 and the post-test had an average value of 63.44. The t-test results obtained a significance value of p = 0.04 <α = 0.05. Based on the results of this study, it shows that the problem-based learning model has an effect on the independence and cognitive learning outcomes of students at MTs. Nurul Hakim, Kediri District, West Lombok Regency.